PENGEMBANGAN GAME EDUCATION BERBASIS ADOBE FLASH PADA MATERI MENGENAL BINATANG PADA KURIKULUM MERDEKA DI TK NEGERI 01 SITIUNG - Estuhono; Sri Yunimar Ningsih; Zahratun Nur (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research is motivated by several things that the researchers found in the initial observations. The purpose of this research is to produce a product in the form of an educational game introduction to educational games based on Adobe Flash on material about animals in an independent curriculum at TK Negeri 01 Sitiung that is valid, practical and effective. . The type of research used is Research and Development with the ADDIE model, namely the stages of analysis, design, development, implementation and evaluation. The data collection instrument in this study was a questionnaire to test validity, practicality and effectiveness. The product validity test was carried out by 3 validators, namely the material validator, language validator and media validator. The practicality test was carried out by 4 class teachers and the effectiveness test was carried out on 6 students. The results of the analysis show that the Animal Introduction Educational Game developed based on the assessment of the media aspect of the Educational Game is in the "very valid" category based on the assessment of the material aspects including the "very valid category". and based on the assessment of the linguistic aspect included in the "very valid" category. The description of the practicality test data based on the teacher's view shows that the Educational Games made are included in the "very practical" category. The description of the effectiveness trial data on students shows that the Educational Games made are included in the very effective category. These results indicate that the Educational Game developed is suitable for use as a learning medium about animals in Sitiung 01 State Kindergarten.